Design and fabrication of biodiesel mixer for the compatibility study of biodiesel blends with automotive part material - A. Sharum, M. S.; Mansur, M. N.; Abdul Patar, M. A.; Nasir, Nurul Fitriah (FAZ Publishing, 2020)
Biodiesel is a way or alternative to replacing pure fossil fuel where it likely going exhaust and may run out totally. Biodiesel is a mixture of sentence percentage of diesel oil and it will combine it with suitable organic substance. However, seems like not all of raw material that will combine with biodiesel compound is suitable and an analysis should be done before a massive production of sector automotive take place by using that raw material. The mixture of biodiesel and raw material usually been done with small beaker which is the testing space is limited. Therefore, this final year project is focusing on design and fabrication a biodiesel mixer which can replace recent testing toward compatibility study of automotive material. In addition, each of criteria of biodiesel mixer needs to be similar to recent analysis method. Each of the specimens can be hang on the biodiesel container in sentence of time to study the material is suitable or not. Besides that, all tools and equipment that being uses in fabrication of biodiesel mixer needs compatibility enough with biodiesel to avoid error while testing took place. Thus, this project will make the researcher done an analysis easier compare to recent method toward compatibility study of biodiesel mixed with automotive material.